When Things Happen - The Story of COVID-19, Palliative Care, and An NGO - Ayda G Nambayan; Rumalie A Corvera; Loyda Amor N Cajucom; Carmel D Vicencio (Elsevier, 2021)
Several natural disasters and the appearance of the coronavirus disease 2019 (COVID-19) pandemic created stressful situations to many health-care workers in the Philippines. New health-related challenges surfaced, and health-care workers felt lost since many of the challenges were either directly or indirectly caused by the fast-spreading coronavirus infections and its variants. Further, the way people die also changed, causing confusion and influencing the Filipino grief and bereavement processes. In response to the need of the health-care workers, a nongovernmental organization (NGO) through its education portal created and offered free webinars, aimed to help health-care workers understand and make sense of what was happening, thus empowering them with knowledge on how to manage the challenges and provide better care to the patients and the community as well. This article relates the process of planning and implementing online webinars during the era of social distancing and COVID-19 pandemic.